Digitalization and the Challenges of Hadith Dissemination in the Modern Era: Digitalisasi dan Tantangan Penyebaran Hadis di Era Modern - Hasanah, Uswatun; Hifni, Ahmad (Institut Agama Islam Negeri Kerinci, 2024)
In this modern era, of course we cannot avoid technology. Increasingly advanced technology has an influence on the world of education, one of which is the science of hadith. Hadith that appear in online or offline digital media have been very easily accessed anywhere, without a clear filtering process to understand them. The digitization of hadith in this modern era certainly has good impacts and challenges that must be accepted by everyone, especially hadith scholars. This article aims to analyze the challenges and opportunities that arise in the use of hadith digitization in the modern era. Using the descriptive-qualitative method, the study analyzes the various media that have developed in hadith studies especially in the online and offline digital world. The results of this discussion show that the digitization of hadith has many challenges due to the easy access to hadith, one of the challenges is the easy spread of false hadith. However, among these challenges there are also opportunities and benefits of the digitization of hadith in the modern era, namely the ease of accessing hadith that used to be still in the hadith books, now changing to digital versions online or offline.